Injection-molded ferrite composite magnet and method for producing the same

CN122889536APending Publication Date: 2026-10-09XINCHANG XINLI ELECTRONIC TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611299949.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-26
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

综上所述,现有技术方案均未能突破“高填充率与高性能不可兼得”的技术瓶颈,其根本原因在于所构建的磁粉-粘结剂界面是静态的、被动的,无法在保证加工流动性的同时,提供足以应对复杂服役条件的强大而稳定的界面结合

Benefits of technology

1.卓越的综合磁性能与超高填充率的统一:动态界面极大地降低了高填充体系下的熔体粘度,使得磁粉填充率可高达92%的同时,磁粉仍能实现良好取向。所得磁体剩余磁感应强度(Br)提升至245-280mT,内禀矫顽力(Hcj)达205-255kA/m,最大磁能积((BH)max)达到12-18kJ/m3,全面超越了静态界面体系的对比例。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122889536A_ABST
    Figure CN122889536A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of magnetic composite materials, in particular to an injection-molded ferrite composite magnet and a preparation method thereof. The composition comprises dynamic covalent bond modified ferrite magnetic powder, polyphenylene sulfide blend containing a dynamic crosslinking network and other additives. First, a silica transition layer and a polymer brush containing a Diels-Alder reaction furan functional group are sequentially constructed on the surface of the ferrite magnetic powder; second, a polyarylene ether ketone containing maleimide and borate ester bonds is prepared and blended with polyphenylene sulfide to form a dynamic crosslinking network; then the modified magnetic powder, the dynamic crosslinking binder and the additives are subjected to high-speed mixing, double-screw melt extrusion granulation; and finally, injection molding is carried out. The product of the application realizes breakthrough magnetic performance, excellent toughness, self-repairing characteristics and dimensional stability under extreme environment at an ultrahigh magnetic powder filling rate, and solves the technical paradox that high filling rate and high performance cannot be compatible which has long plagued the field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of magnetic composite materials technology, specifically to an injection-molded ferrite composite magnet and its preparation method. Background Technology

[0002] Bonded ferrite injection-molded magnets are key functional components in modern electronics and micromotors, and their performance directly determines motor efficiency, sensor accuracy, and device reliability. Currently, the core challenge in this technology lies in the continuous increase of magnetic powder filling rate to improve magnetic properties. However, this inevitably leads to a reduction in the proportion of polymer binder, causing a series of chain reactions such as deteriorated processing fluidity, increased internal stress, and weak interfacial bonding. Existing technologies mostly focus on mitigating this contradiction by optimizing the coupling agent coating process or adding various additives.

[0003] Chinese invention patent CN106317862A uses polyolefin to modify polyamide and employs a two-step granulation method. Although it improves toughness and water absorption to some extent, the polyamide matrix has insufficient temperature resistance. Moreover, the modification method is still limited to physical blending and simple interfacial physical adsorption, resulting in limited improvement in interfacial bonding force. Under high load or thermal cycling conditions, interfacial debonding is likely to occur.

[0004] Chinese invention patent CN117393306A focuses on improving processing fluidity by repeatedly and intermittently spraying coupling agents and adding flowable resins. However, its technical essence remains the optimization of physical coating effects and reliance on the lubricating effect of small-molecule additives. It fails to strengthen the interface from a chemical perspective, and the addition of additives may bring risks of long-term aging migration and performance degradation. In summary, existing technical solutions have failed to overcome the technical bottleneck of "high filling rate and high performance being mutually exclusive." The fundamental reason is that the constructed magnetic powder-binder interface is static and passive, unable to provide a strong and stable interfacial bond sufficient to cope with complex service conditions while ensuring processing fluidity.

[0005] Therefore, developing a novel interface structure capable of proactively adapting to changes in processing and service environments and achieving on-demand performance switching has become a pressing technical challenge in this field. Against this backdrop, this invention proposes a novel solution based on cutting-edge dynamic covalent chemistry principles. Summary of the Invention

[0006] The purpose of this invention is to provide an injection-molded ferrite composite magnet and its preparation method.

[0007] This invention relates to the field of magnetic composite materials technology, specifically to an injection-molded ferrite composite magnet with a dynamically adaptive interface and its preparation method. The composite magnet is made from the following raw materials in weight percentages: 83%-92% dynamically covalently modified ferrite magnetic powder, 7%-15.5% polyphenylene sulfide blend containing a dynamically cross-linked network, and 0.5%-1.5% other additives. The preparation method includes: first, sequentially constructing a silica transition layer and a polymer brush containing Diels-Alder (DA) reactive furan functional groups on the surface of the ferrite magnetic powder; second, preparing a polyaryletherketone containing both maleimide and borate ester bonds, and blending it with polyphenylene sulfide to form a dynamically cross-linked network; then, mixing the modified magnetic powder, dynamically cross-linked binder, and additives at high speed, followed by twin-screw melt extrusion granulation, and finally injection molding. This invention creates a "dynamically adaptive interface" by introducing reversible DA covalent bonds and borate ester bonds at the interface between the magnetic powder and the binder, and in the binder matrix. The interface can be reversibly fractured at high processing temperatures, greatly improving fluidity; it can reform at service temperatures, providing superior interfacial bonding and damage repair capabilities. This enables the final product to achieve breakthrough magnetic properties, excellent toughness, self-healing characteristics (mechanical property recovery rate ≥85% after repair), and dimensional stability under extreme environments, even with ultra-high magnetic powder filling rates. This solves the long-standing technical paradox of the incompatibility between high filling rates and high performance in this field.

[0008] An injection-molded ferrite composite magnet is prepared from the following raw materials in weight percentages: 83%-92% dynamically covalently modified ferrite magnetic powder, 7%-15.5% polyphenylene sulfide blend containing a dynamically cross-linked network, 0.2%-0.8% antioxidant, and 0.3%-0.7% lubricant.

[0009] Preferably, the dynamically covalently modified ferrite magnetic powder is MFe with a polymer brush containing furan groups grafted onto its surface through a silica transition layer. 12 O 19 Magnetic powder, wherein M is any element of barium or strontium.

[0010] Preferably, the polyphenylene sulfide blend containing a dynamic crosslinking network is a blend of polyphenylene sulfide and polyaryletherketone containing dynamic covalent bonds, wherein the polyaryletherketone chain simultaneously contains maleimide groups and borate ester bonds as components of the Diels-Alder reaction.

[0011] Preferably, the polymer brush containing furan groups is generated by grafting furan methacrylate via atom transfer radical polymerization (ATRP), and the molecular weight of the polymer brush is 5000-20000 g / mol.

[0012] Preferably, the polyaryletherketone containing dynamic covalent bonds has maleimide groups located on the polymer side chain, with a content of 0.5-2 mmol / g polymer; and borate ester bonds located on the polymer main chain, introduced by copolymerization of bis(catechol)boronic acid monomer and difluoro monomer.

[0013] A method for preparing an injection-molded ferrite composite magnet includes the following steps: (1) Multi-level surface modification of magnetic powder: a) SiO2 transition layer coating: A layer of amorphous silicon dioxide with a thickness of 20-50 nm is coated on the surface of ferrite magnetic powder using the Stöber method; b) ATRP initiator fixation: ATRP initiators containing trimethoxysilane (such as BiBB-TMS) are used to react with the hydroxyl groups of the SiO2 layer to anchor the initiator to the magnetic powder surface; c) Polymer brush grafting: Using furan methacrylate as a monomer, a polymer brush containing furan groups is grown on the surface of the magnetic powder through surface-initiated ATRP to obtain dynamically covalently modified ferrite magnetic powder. (2) Preparation of dynamic crosslinking adhesive: a) Synthesis of polyarylether ketone (PAEK-MI-B) containing maleimide and borate ester: It is copolymerized from 4,4'-difluorobenzophenone, bis(catechol) borate monomer and maleimide-containing bisphenol monomer via nucleophilic substitution polycondensation reaction. b) Blending: PAEK-MI-B synthesized in step a) is melt-blended and granulated with polyphenylene sulfide at a mass ratio of 0.18-0.43 in a twin-screw extruder to obtain a polyphenylene sulfide blend containing a dynamic cross-linked network; (3) Mixing and dynamic cross-linking granulation: The modified magnetic powder obtained in step (1), the dynamic cross-linking binder obtained in step (2), the antioxidant and the lubricant are mixed evenly in a high-speed mixer, and then melt-mixed and extruded and granulated by a twin-screw extruder at 240-270℃ (this temperature is higher than the reverse reaction temperature of DA reaction, so that the DA bond at the interface is broken); (4) Injection molding and interface “healing”: The granules obtained in step (3) are injection molded. After injection molding, the magnet is annealed at 110-130℃ for 1-2 hours to allow the furan groups on the surface of the magnetic powder to undergo a Diels-Alder reaction with the maleimide groups in the binder, and to reform a strong covalent bond interface network.

[0014] Preferably, in step (1)c), the ATRP reaction temperature is 70°C and the reaction time is 6-12 hours, so as to precisely control the molecular weight and density of the polymer brush.

[0015] Preferably, in step (2)a), the maleimide-containing bisphenol monomer is prepared by reacting allyl bisphenol A with maleimide via the "Ene" reaction.

[0016] Preferably, in step (3), the screw speed of the granulation process is 80-100 rpm to ensure thorough mixing while avoiding excessive mechanical shear degradation of dynamic covalent bonds.

[0017] Preferably, in step (4), a rotating magnetic field is used for orientation during injection molding, and the orientation field strength is 1.8-2.8T.

[0018] The injection-molded ferrite composite magnet prepared by this invention can be used in the preparation of high-reliability, long-life micro-motors, robot joint servo motors, or aerospace sensor magnets.

[0019] The injection-molded ferrite composite magnet prepared by this invention can achieve self-repair of its mechanical properties through heat treatment at 130℃ for 2 hours after being subjected to microscopic damage. After repair, its impact strength is restored to more than 85% of the original value.

[0020] The core innovation of this invention lies in abandoning the traditional static, permanent interface design approach and instead constructing a "dynamic adaptive interface" that can respond to changes in processing and service conditions. This design is inspired by dynamic covalent chemistry and self-healing materials in the field of polymers, and creatively applies them to solve the inherent contradictions of highly filled composite magnets.

[0021] (1) "Programmable" magnetic powder surface: from static anchoring to dynamic reaction point.

[0022] Instead of simply viewing magnetic powder as a coated object, we program it as a platform with active chemical reactions.

[0023] First stage: A stable SiO2 transition layer. A uniform inorganic layer is constructed on the surface of the magnetic powder using the classic Stöber method. This not only provides a substrate that is firmly bonded to the magnetic powder, but the silanol groups on its surface are also an ideal starting point for subsequent organic reactions, avoiding the inhomogeneity of direct reactions with the hydroxyl groups on the magnetic powder surface.

[0024] The second stage: a controllable active initiation layer. A silane-containing ATRP initiator is introduced and covalently fixed onto the SiO2 layer. This step achieves a uniform, high-density distribution of initiation sites on the surface, laying the foundation for precise polymerization in the next step.

[0025] The third stage involves growing polymer brushes with specific functional groups. Through surface-initiated ATRP, the molecular weight and distribution are precisely controlled to grow polymer molecular brushes with furan functional groups. This polymer brush not only greatly improves the dispersibility of the magnetic powder, but its terminal furan groups also become "dynamic chemical anchors" that can undergo Diels-Alder (DA) reactions with the binder.

[0026] (2) Binder network with “intelligent” response capability: dual dynamic covalent bond synergy.

[0027] The adhesive is no longer an inert matrix, but a smart network with dynamic responses both internally and at the interface.

[0028] Matrix dynamic network (boronic acid ester bonds): We designed and synthesized a polyarylether ketone (PAEK-MI-B) with boronic acid ester bonds in the main chain. The boronic acid ester bonds are stable at room temperature, giving the material strength; they can reversibly break and recombine under shear force or specific temperatures, which endows the melt with excellent shear thinning behavior and thixotropic rheological properties, greatly improving the processing fluidity under high filling conditions, and achieving intrinsic damage repair through bond recombination after molding.

[0029] Interfacial dynamic bridging (Diels-Alder reaction): Maleimide groups are introduced into the side chains of PAEK-MI-B as the other half of the DA reaction. At the high temperatures (>120℃) of granulation and injection molding, the DA bonds between the furan on the magnetic powder surface and the maleimide in the binder undergo reversible breakage, resulting in a sharp drop in interfacial viscosity, as if the bond has been temporarily "released," making the magnetic powder particles easier to flow and orient. When the product cools and undergoes subsequent annealing, these bonds reversibly reform, building a strong, covalent "bridge" at the interface, achieving an interfacial strength far exceeding that of physical adsorption and ordinary silane coupling.

[0030] (3) Collaborative working mechanism: decoupling and unification of processability and ultimate performance.

[0031] The core advantage of this dual dynamic system lies in its ability to decouple the two originally contradictory requirements of "good flowability required for processing" and "ultra-high strength / stability required for service" in time and achieve their unification through chemical means.

[0032] During processing: High temperature and shearing cause the DA bond at the interface and the borate ester bond in the matrix to break simultaneously, resulting in excellent system fluidity.

[0033] During service: the interface DA bond and the matrix borate ester bond reform, forming a robust network of interwoven covalent and dynamic bonds, providing excellent mechanical properties, fatigue resistance and unique self-healing ability.

[0034] This interface-matrix co-design based on dynamic covalent chemistry is something that those skilled in the art could not easily conceive of using only conventional surface treatment or simple blending knowledge. It represents a paradigm shift in solving the interface problem of highly filled composite materials.

[0035] Beneficial technical effects of the present invention: This invention achieves the following groundbreaking technical effects by constructing a dynamic adaptive interface: 1. A combination of superior overall magnetic properties and ultra-high filler ratio: The dynamic interface significantly reduces the melt viscosity in high-filler systems, allowing for a magnetic powder filler ratio of up to 92% while maintaining good orientation. The resulting magnet exhibits a remanent magnetic induction (Br) of 245-280 mT, intrinsic coercivity (Hcj) of 205-255 kA / m, and a maximum energy product ((BH)max) of 12-18 kJ / m. 3 It completely surpasses the proportion of static interface systems.

[0036] 2. Revolutionary Mechanical Properties and Self-Healing Capability: Based on the robust network formed by dynamic covalent bonds in the interface and matrix at service temperatures, the magnet exhibits extremely high mechanical strength and toughness. Radial crushing force remains stable above 260N, and impact strength reaches 22-25kJ / m. 2 Of particular note is that this magnet possesses intrinsic self-healing properties. Damage such as microcracks that occur during use can be repaired through simple heat treatment (130℃ / 2h). After repair, the mechanical properties recover more than 85%, greatly extending the product's service life in harsh environments.

[0037] 3. Excellent processing flowability and moldability: Under the high temperature of granulation and injection molding, the reversible breakage of dynamic covalent bonds enables the composite system to exhibit excellent shear thinning behavior. The melt index (MI) is significantly improved compared with the traditional system with the same filling rate, and the mold filling ability is significantly enhanced, effectively eliminating defects such as incomplete injection and internal stress cracking that are common in high-filled magnets.

[0038] 4. Exceptional dimensional stability and durability: Due to the ability of the dynamic covalent bond network to dissipate and redistribute stress through reversible reactions, the magnet exhibits a magnetic flux attenuation rate of less than 2% after thermal aging (150℃, 1000h), demonstrating superior stability under extreme conditions and meeting the highest requirements for material reliability in the automotive, aerospace and other fields. Attached Figure Description

[0039] Figure 1 This is a schematic diagram of the multi-level modification structure of the ferrite magnetic powder surface modified by dynamic covalent bonds according to the present invention (from inside to outside: ferrite magnetic powder 101 → SiO2 transition layer 102 → ATRP initiator layer 103 → polymer brush containing furan groups 104).

[0040] Figure 2 This is a schematic diagram of the structure of the polyphenylene sulfide blend (PPS / PAEK-MI-B) containing a dynamic crosslinking network of the present invention, showing the borate ester bond of the main chain and the maleimide group of the side chain (201 represents the borate ester bond (B-O) of the main chain, 202 represents the polyphenylene sulfide (PPS) segment, 203 represents the dynamic covalent crosslinking point, 204 represents the maleimide group (MI) of the side chain, and 205 represents the polyaryletherketone (PAEK) segment).

[0041] Figure 3 The diagram shows the process flow of the preparation method of the present invention, highlighting the two core steps of "dynamic cross-linking granulation" and "interface healing after injection molding". Detailed Implementation

[0042] Before further describing specific embodiments of the present invention, it should be understood that the scope of protection of the present invention is not limited to the specific embodiments described below; it should also be understood that the terminology used in the embodiments of the present invention is for describing specific embodiments and not for limiting the scope of protection of the present invention. Test methods in the following embodiments that do not specify specific conditions are generally performed under conventional conditions or as recommended by the respective manufacturers.

[0043] When numerical ranges are given in the embodiments, it should be understood that, unless otherwise stated in this invention, both endpoints of each numerical range and any value between the two endpoints may be selected. Unless otherwise defined, all technical and scientific terms used in this invention have the same meaning as commonly understood by those skilled in the art. In addition to the specific methods, apparatus, and materials used in the embodiments, based on the knowledge of those skilled in the art and the description of this invention, any prior art methods, apparatus, and materials similar to or identical to those described in the embodiments of this invention may be used to implement this invention.

[0044] Unless otherwise stated, the test methods, detection methods and preparation methods disclosed in this invention all adopt conventional techniques in this technical field.

[0045] Example 1

[0046] First, multi-stage surface modification of the magnetic powder was performed. One kilogram of strontium ferrite magnetic powder (SrFe) with an average particle size of 1.5 μm was taken. 12 O 19The SiO2@SrFe was dispersed in a mixed solution of 200 mL anhydrous ethanol, 50 mL deionized water, and 10 mL concentrated ammonia. 5 mL of tetraethyl orthosilicate (TEOS) was slowly added dropwise under mechanical stirring. The reaction was carried out at 40 °C for 6 hours, resulting in a uniform silica transition layer of approximately 30 nm thickness on the magnetic powder surface using the Stöber method. After centrifugation, washing, and vacuum drying at 80 °C, the SiO2@SrFe was ready for use. Subsequently, ATRP initiator fixation was performed to immobilize the SiO2@SrFe. 12 O 19 Magnetic powder was dispersed in 200 mL of toluene, and 3 g of 2-bromo-2-methyl-N-(3-(trimethoxysilyl)propyl)propionamide (BiBB-TMS), a trimethoxysilane-terminated ATRP initiator, was added. The mixture was refluxed at 90 °C for 12 hours under nitrogen protection to firmly anchor the initiator to the magnetic powder surface via siloxane bonds, yielding Br-Initiator@SiO2@SrFe. 12 O 19 Then, polymer brush grafting was performed. 1 gram of the above magnetic powder, 2 grams of furan methacrylate (FMA) monomer, and 20 mg of cuprous bromide / 40 mg of pentamethyldiethylenetriamine catalytic system were dispersed in 50 mL of N,N-dimethylformamide (DMF). Surface-initiated atom transfer radical polymerization (SI-ATRP) was carried out for 8 hours in an oil bath at 70°C under nitrogen protection. By precisely controlling the monomer to initiator ratio, a molecular weight of approximately 10000 g / mol and a grafting density of approximately 0.3 chains / nm were obtained. 2 Magnetic powder modified with polyfuran methacrylate polymer brush (PFMA-brush@SiO2@SrFe) 12 O 19 Next, a dynamic crosslinking binder was prepared by nucleophilic substitution condensation polymerization to form a polyarylether ketone containing dynamic covalent bonds. 4,4'-difluorobenzophenone (10 mmol), a self-made bisphenol monomer containing borate ester bonds (5 mmol), and a bisphenol monomer containing maleimide side chain groups (5 mmol) were reacted in N-methylpyrrolidone (NMP) at 180°C for 12 hours using potassium carbonate as a catalyst to obtain PAEK-MI-B with a number average molecular weight of approximately 35,000 and a maleimide content of 1.2 mmol / g. This was then melt-blended and granulated with polyphenylene sulfide (PPS, intrinsic viscosity 0.65 dL / g) at a mass ratio of 20 / 80 in a twin-screw extruder (300°C, screw speed 100 rpm). Finally, a composite magnet was prepared by mixing 88% PFMA-brush@SiO2@SrFe... 12 O 19Magnetic powder, 11.2% PPS / PAEK-MI-B blended granules, 0.3% antioxidant 245, and 0.5% ethylene bis-stearamide (EBS) lubricant were mixed in a high-speed mixer at 800 rpm for 15 minutes. Then, the mixture was melt-extruded and granulated in a twin-screw extruder (zone 1: 240℃, zone 2: 250℃, zone 3: 255℃, die head: 250℃, screw speed: 90 rpm). The resulting granules were then molded into standard test strips and multipole magnetic rings in an injection molding machine (barrel temperature: 270℃, mold temperature: 100℃, injection pressure: 100MPa, holding pressure: 80MPa). During the molding process, a 2.2T rotating magnetic field was applied for orientation. Finally, the injection-molded products were annealed in a 120℃ circulating air oven for 1.5 hours to complete the interface Diels-Alder reaction and achieve interface "healing".

[0047] Example 2

[0048] First, the surface of the magnetic powder was modified. Following the method in Example 1, a silica transition layer was coated onto the surface of 1 kg of strontium ferrite magnetic powder, and an ATRP initiator was fixed. Then, during the surface-initiated atom transfer radical polymerization stage, the reaction conditions were adjusted. 2.5 g of furan methacrylate monomer was used, and the reaction was carried out at 70°C for 12 hours. By extending the reaction time and precisely controlling the monomer conversion rate, a molecular weight of approximately 15000 g / mol and a grafting density of approximately 0.25 chains / nm were obtained. 2 Magnetic powder modified with polyfuran methacrylate polymer; in the preparation of dynamic crosslinking adhesive, the synthesis formula of polyarylether ketone was adjusted, and 4,4'-difluorobenzophenone (10 mmol), bisphenol monomer containing borate ester bond (6 mmol) and bisphenol monomer containing maleimide side chain group (4 mmol) were added. The polymer brush was copolymerized to obtain PAEK-MI-B with a number average molecular weight of approximately 32,000 and a maleimide content of 0.8 mmol / g. This was then melt-blended and granulated with polyphenylene sulfide (PPS, intrinsic viscosity 0.65 dL / g) at a mass ratio of 0.18 in a twin-screw extruder (300°C, screw speed 100 rpm). For the preparation of the composite magnet, 85% of the polymer brush-modified magnetic powder, 14.2% of the PPS / PAEK-MI-B blend granules, 0.3% of antioxidant 245, and 0.5% of ethylene bis-stearamide lubricant were mixed in a high-speed mixer. The twin-screw extrusion granulation process parameters were the same as in Example 1. During injection molding, the orientation field strength was adjusted to 2.0T, and the annealing conditions after injection molding were 120°C / 1.5 hours. In this example, by increasing the molecular weight of the polymer brush to reduce the surface energy of the magnetic powder and adjusting the proportion of dynamic covalent bonds in the binder, the processing fluidity of the system was further optimized while ensuring the interfacial bonding strength.

[0049] Example 3

[0050] In the magnetic powder surface modification stage, after coating 1 kg of strontium ferrite magnetic powder with a silica transition layer and fixing the ATRP initiator, 1.8 g of furan methacrylate monomer was used in the surface-initiated atom transfer radical polymerization stage. The reaction was carried out at 70 °C for 6 hours, controlling the polymer brush molecular weight to be approximately 8000 g / mol and the grafting density to be approximately 0.35 chains / nm. 2 In the preparation of the dynamic crosslinking binder, the feed ratio of polyaryletherketone monomers was adjusted, and 4,4'-difluorobenzophenone (10 mmol), bisphenol monomers containing borate ester bonds (4 mmol), and bisphenol monomers containing maleimide side chain groups (6 mmol) were copolymerized to obtain PAEK-MI-B with a number average molecular weight of approximately 38,000 and a maleimide content of 1.5 mmol / g. This was then melt-blended and granulated with polyphenylene sulfide at a mass ratio of 25 / 75 in a twin-screw extruder. For the preparation of the composite magnet, 90% polymer-modified magnetic powder, 9.2% PPS / PAEK-MI-B blended granules, 0.3% antioxidant 245, and 0.5% ethylene bis-stearamide lubricant were mixed by weight percentage. The head temperature during twin-screw extrusion granulation was adjusted to 255°C, and other process parameters were the same as in Example 1. During injection molding, the orientation field strength was increased to 2.5. To overcome the orientation resistance under high filling rate, the annealing conditions after injection molding remain unchanged; in this embodiment, by increasing the magnetic powder filling rate to 90% and correspondingly increasing the maleimide content in the binder, sufficient dynamic covalent crosslinking points are still available under high filling rate, thereby achieving further improvement in magnetic properties.

[0051] Comparative Example 1 The magnetic powder treatment only involved conventional silane coupling agent modification. One kilogram of strontium ferrite magnetic powder was coated with SiO2 using the same process as in Example 1, and then treated with an ethanol solution of silane coupling agent KH-560 at a weight ratio of 3%. The powder was dried at 80°C for 4 hours to obtain KH-560@SiO2@SrFe. 12 O 19 Magnetic powder; the binder is a blend of ordinary polyaryletherketone (PAEK) and polyphenylene sulfide (PPS), which contains no dynamic covalent bonds. PAEK and PPS are melt-blended and granulated in a twin-screw extruder at a mass ratio of 20 / 80. The composite magnet is prepared by adding 88% KH-560@SiO2@SrFe by weight. 12 O 19 Magnetic powder, 11.2% PPS / PAEK blended granules, 0.3% antioxidant 245 and 0.5% ethylene bis-stearamide lubricant were mixed, and the twin-screw granulation and injection molding process parameters were exactly the same as in Example 1. After injection molding, the mixture was also annealed at 120°C for 1.5 hours. This comparative example was used to verify the performance difference between the static interface of the traditional silane coupling agent and the dynamic covalent interface of the present invention.

[0052] Comparative Example 2 The magnetic powder treatment was exactly the same as in Example 1, using PFMA-brush@SiO2@SrFe 12 O 19 In the preparation of magnetic powder and binder, polyaryletherketone (PAEK-MI) containing only maleimide and no borate ester bonds was synthesized. 4,4'-difluorobenzophenone (10 mmol) and bisphenol monomer (10 mmol) containing maleimide side-chain groups were copolymerized to obtain PAEK-MI with a number average molecular weight of approximately 35,000 and a maleimide content of 1.2 mmol / g. This was then melt-blended and granulated with polyphenylene sulfide at a mass ratio of 20 / 80. For the preparation of the composite magnet, 88% polymer-modified magnetic powder, 11.2% PPS / PAEK-MI blended granules, 0.3% antioxidant 245, and 0.5% ethylene bis-stearamide lubricant were mixed by weight percentage. The twin-screw granulation and injection molding process parameters were exactly the same as in Example 1, and annealing was performed after injection molding. This comparative example was used to verify the contribution of the dynamic covalent bond network of borate esters to the material's processing fluidity and self-healing properties.

[0053] Comparative Example 3 The specific implementation process of Comparative Example 3 refers to the formulation and process of Example 1 in the prior art document (CN117393306A): 89 parts by weight of strontium ferrite powder, 9.5 parts by weight of nylon 6, 0.5 parts by weight of KH560 silane coupling agent, 0.5 parts by weight of nylon 12 flow resin, and 0.5 parts by weight of additives (of which PEG1000 accounts for 0.2%, 1098 antioxidant accounts for 0.1%, and EBO lubricant accounts for 0.2%). In the preparation process, after the magnetic powder is added to a high-speed mixer and pre-dispersed for 10 minutes, it is then... The mixture of coupling agent and alcohol was added three times through an atomizing device, each time stirred at 500 rpm for 5 minutes, with a 5-minute interval between stirring at 200 rpm. Then, the binder, dispersant, lubricant, antioxidant, and flow resin were added to a high-speed mixer and stirred at 800 rpm for 30 minutes, with the temperature controlled not to exceed 120°C. Finally, the composite powder was extruded and granulated at 230°C to obtain injection-molded magnet granules. This comparative example serves as a comparison with the prior art to highlight the technical advantages of the dynamic interface design of this invention.

[0054] Comparative Example 4 All raw material formulations are identical to those in Example 1, including the use of 88% PFMA-brush@SiO2@SrFe. 12 O 19The magnetic powder and 11.2% PPS / PAEK-MI-B blended granules, along with the twin-screw granulation and injection molding process parameters, were kept consistent with those in Example 1. The only difference was that the annealing process at 120°C for 1.5 hours after injection molding was completely omitted, and the injection-molded products were directly tested for performance after natural cooling at room temperature. This comparative example was used to verify the key role of the interfacial Diels-Alder reaction initiated by post-injection heat treatment in building a robust interfacial network, revealing the necessity of the "healing" process in dynamic covalent chemistry.

[0055] Performance testing The following are the testing standards: Magnetism (Br), coercivity (Hcb), intrinsic coercivity (Hcj), and maximum energy product ((BH)max) are based on standard GB / T3217-2013; radial crushing force is based on GB / T 44656-2024. Table 1 shows the performance test results of various embodiments of the present invention.

[0056] Table 2 shows the relevant performance test results of each comparative example of the present invention.

[0057] Analysis of possible causes of differences in test results: Comparative Example 1 to Comparative Example 2: The Comparative Example 2 significantly outperforms Comparative Example 3 in terms of magnetic properties, mechanical properties, and durability. This directly demonstrates the overwhelming advantage of the dynamic covalent interface (polymer brush + DA reaction) over the traditional static interface (silane coupling agent). The static interface of Comparative Example 1 cannot provide sufficient bonding force, resulting in slightly poorer magnetic powder orientation, and the interface is prone to becoming a failure source under stress and heat.

[0058] Comparing Example 1 and Comparative Example 2: Example 1 showed significantly better processing fluidity (melt index) than Comparative Example 2. This is attributed to the shear thinning effect caused by the reversible breakage of borate ester bonds under shear and high temperature. Comparative Example 2 lacked the dynamic network of borate esters, resulting in a higher melt viscosity. Meanwhile, Example 1 exhibited slightly higher self-healing efficiency, indicating a synergistic effect between borate ester bonds and DA bonds during the repair process.

[0059] Comparative Example 1 and Comparative Example 3: The Comparative Example 1 significantly outperforms Comparative Example 3, which represents the prior art, in terms of mechanical properties and durability. This indicates that the dynamic chemical interface design of the present invention is inherently superior to the traditional approach of optimizing physical coating and adding flow aids, the latter of which cannot achieve a strong covalent interface and self-healing function.

[0060] Comparative Example 1 and Comparative Example 4: This is the most crucial comparison. The properties of Comparative Example 4 (unannealed), especially its mechanical properties (impact strength, crushing force) and thermal stability, are significantly lower than those of Example 1. This eloquently demonstrates that post-injection molding annealing to complete the interfacial DA reaction is an indispensable and crucial step in constructing the final stable interfacial network. Without annealing, the magnetic powder and binder rely primarily on physical interactions for bonding, resulting in significantly reduced performance. This step is easily overlooked by those skilled in the art based on conventional understanding, highlighting the non-obviousness of the process of this invention.

[0061] In summary, this invention successfully resolves the inherent contradictions of highly filled composite magnets through a complex, multi-level dynamic covalent chemical design. Its technical effects are substantial and significant, and cannot be easily predicted by those skilled in the art.

[0062] Finally, it should be noted that the above embodiments are used to illustrate the technical solutions of the present invention and not to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.

Claims

1. A type of injection-molded ferrite composite magnet, characterized in that, It is prepared from the following raw materials in weight percentage: 83%-92% dynamically covalently modified ferrite magnetic powder, 7%-15.5% polyphenylene sulfide blend containing a dynamic cross-linked network, 0.2%-0.8% antioxidant, and 0.3%-0.7% lubricant.

2. The injection-molded ferrite composite magnet according to claim 1, characterized in that: The dynamically covalently modified ferrite magnetic powder is MFe with a polymer brush containing furan groups grafted onto its surface through a silica transition layer. 12 O 19 Magnetic powder, wherein M is any element of barium or strontium.

3. The injection-molded ferrite composite magnet according to claim 1, characterized in that: The polyphenylene sulfide blend containing a dynamic cross-linked network is a blend of polyphenylene sulfide and polyarylether ketone containing dynamic covalent bonds, wherein the polyarylether ketone chain simultaneously contains maleimide groups and borate ester bonds as components of the Diels-Alder reaction.

4. The injection-molded ferrite composite magnet according to claim 2, characterized in that: The furan-containing polymer brush is generated by grafting furan methacrylate via atom transfer radical polymerization, and the molecular weight of the polymer brush is 5000-20000 g / mol.

5. The injection-molded ferrite composite magnet according to claim 3, characterized in that: The polyaryletherketone containing dynamic covalent bonds has maleimide groups located on the polymer side chain, with a content of 0.5-2 mmol / g polymer; the borate ester bonds are located on the polymer main chain and are introduced by copolymerization of bis(catechol)boronic acid monomer and difluoro monomer.

6. A method for preparing an injection-molded ferrite composite magnet as described in any one of claims 1-5, characterized in that, Includes the following steps: (1) Multi-level surface modification of magnetic powder: a) SiO2 transition layer coating: An amorphous silica layer with a thickness of 20-50 nm is coated on the surface of ferrite magnetic powder using the Stöber method. The amount of tetraethyl orthosilicate used is 4-6 mL per kilogram of ferrite magnetic powder. The reaction is carried out in a mixed solution composed of anhydrous ethanol, deionized water and concentrated ammonia at a reaction temperature of 35-45℃ for 5-7 hours. b) ATRP initiator fixation: ATRP initiators containing trimethoxysilane are used to react with the hydroxyl groups of the SiO2 layer to anchor the initiator on the surface of the magnetic powder. The amount of ATRP initiator is 2.5-3.5 g per kilogram of ferrite magnetic powder. The reaction is carried out in toluene solvent under reflux at 85-95°C for 10-14 hours. c) Polymer brush grafting: Using furan methacrylate as a monomer, a polymer brush containing furan groups is grown on the surface of magnetic powder via surface-initiated ATRP to obtain dynamically covalently modified ferrite magnetic powder. The amount of furan methacrylate monomer used is 1.8-2.5 kg per kilogram of ferrite magnetic powder. The reaction is carried out in N,N-dimethylformamide solvent with cuprous bromide / pentamethyldiethylenetriamine as a catalyst system at 65-75℃ for 6-12 hours. (2) Preparation of dynamic crosslinking adhesive: a) Synthesis of polyarylether ketones containing maleimide and borate esters: The polyarylether ketones are copolymerized from 4,4'-difluorobenzophenone, bis(catechol)boronic acid monomer and maleimide-containing bisphenol monomer via nucleophilic substitution polycondensation reaction, wherein the molar ratio of the three monomers is 4,4'-difluorobenzophenone: bis(catechol)boronic acid monomer: maleimide-containing bisphenol monomer 10:(4-6):(4-6). The reaction is carried out in N-methylpyrrolidone solvent with potassium carbonate as catalyst at 170-190℃ for 10-14 hours. b) Blending: PAEK-MI-B synthesized in step a) is melt-blended and granulated with polyphenylene sulfide at a mass ratio of 0.18-0.43 in a twin-screw extruder to obtain a polyphenylene sulfide blend containing a dynamic cross-linked network; (3) Mixing and dynamic cross-linking granulation: The modified magnetic powder obtained in step (1), the dynamic cross-linking binder obtained in step (2), the antioxidant and the lubricant are mixed evenly in a high-speed mixer, and then melt-mixed and extruded and granulated at 240-270℃ by a twin-screw extruder; (4) Injection molding and interface "healing": The granules obtained in step (3) are injection molded. After injection molding, the magnet is annealed at 110-130℃ for 1-2 hours to allow the furan groups on the surface of the magnetic powder to undergo a Diels-Alder reaction with the maleimide groups in the binder, and to reform a strong covalent bond interface network.

7. The method for preparing an injection-molded ferrite composite magnet according to claim 6, characterized in that: In step (1)c), the ATRP reaction temperature is 70±2℃ and the reaction time is 6-12 hours to precisely control the molecular weight and density of the polymer brush.

8. The method for preparing an injection-molded ferrite composite magnet according to claim 6, characterized in that: In step (2)a), the maleimide-containing bisphenol monomer is prepared by the "Ene" reaction of allyl bisphenol A and maleimide, wherein the molar ratio of allyl bisphenol A to maleimide is 1:(1.0-1.2).

9. The method for preparing an injection-molded ferrite composite magnet according to claim 6, characterized in that: In step (3), the screw speed of the granulation process is 80-100 rpm, and the temperature of each zone of the twin-screw extruder is set as follows: Zone 1 235-245℃, Zone 2 245-255℃, Zone 3 250-260℃, and Die head 245-255℃.

10. A method for preparing an injection-molded ferrite composite magnet according to claim 6, characterized in that: In step (4), a rotating magnetic field is used for orientation during injection molding, with an orientation field strength of 1.8-2.8T. The injection molding process parameters are: barrel temperature 260-280℃, mold temperature 90-110℃, injection pressure 90-110MPa, and holding pressure 70-90MPa.

Citation Information

Patent Citations

  • High-performance polyamide / ferrite magnetic composite material and preparation method thereof

    CN106317862A

  • Injection molding magnet and preparation method thereof

    CN117393306A